Blank beam fabrication of regenerated type ia gratings - Kalli, Kyriacos; Simpson, George D.; Zhou, Kaiming; Zhang, Lin; Bennion, Ian (My University, 2004)
We demonstrate an idealized method for the fabrication of regenerated type IA fibre Bragg gratings using commonly available apparatus. We use this technique to show that gratings written in the same fibre with the same period may have central wavelengths which are 14.4 nm apart and have an + 11.5% and - 1.2% difference in temperature and strain coefficients, respectively. We use these results to show that temperature compensated dual grating sensor heads, of an arbitrary length, may be quickly and consistently manufactured.
Keywords: Bragg gratings; Optical fibers; Fibers